Social support and psychological wellbeing among urbanites during the pandemic: mattering and life satisfaction - Jun Kit Tan; Kususanto Ditto Prihadi; Prakrisno Satrio (International Journal of Public Health Science (IJPHS), 2022)
The change of social interaction pattern amidst the implementation of social distancing policies during the pandemic had altered the way individuals evaluated themselves and their social environment, including the way they develop perceived social support (PSS) that would lead to another change in the way they develop their satisfaction with life (SWL). This might have affected the development of their psychological wellbeing (PWB), which is highly contingent upon psychosocial constructs. Another variable that might alter the formation of PWB is the sense that we matter to others (Mattering), which was also altered by the limitation of in-person interactions. We purposively recruited 403 Malaysian urban adults affected by the social distancing policies by having to study or work from home, to respond to our survey in order to test the hypothesis that the SWL would fully mediate the association between PSS and PWB among individuals with higher levels of mattering. The results of the bootstrap analysis with 5,000 samples and 95% confident interval supported our hypothesis, with a caveat that the mediation of SWL also occurred among individuals with moderate levels of mattering. PSS was still a significant predictor of PWB when controlling for mattering and SWL, which indicated that the mediation of SWL was only partially occurred.